2021
DOI: 10.1055/s-0041-1722987
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Cochlear Implant Outcomes with Short-Term Aural Rehabilitation

Abstract: Background Increasing numbers of adults are receiving cochlear implants (CIs) and many achieve high levels of speech perception and improved quality of life. However, a proportion of implant recipients still struggle due to limited speech recognition and/or greater communication demands in their daily lives. For these individuals a program of aural rehabilitation (AR) has the potential to improve outcomes. Purpose The study investigated the effects of a short-term AR intervention on speech recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 29 publications
3
12
0
15
Order By: Relevance
“…Social HHI showed statistically significant improvement for the AR group at 1 week posttreatment [t(17) = 2.62, p = 0.018] with large effect size (1.18). This pattern of medium to large effect sizes for HHI results is consistent with those found in Bernstein, Brewer et al 27 COSI (Table III, Fig. 3)COSI means at pretest were not significantly different between groups (Cohen's d, Goal 1: 0.10, Goal 2: 0.10, Goal 3: 0.39).…”
Section: Outcome Measuressupporting
confidence: 90%
See 1 more Smart Citation
“…Social HHI showed statistically significant improvement for the AR group at 1 week posttreatment [t(17) = 2.62, p = 0.018] with large effect size (1.18). This pattern of medium to large effect sizes for HHI results is consistent with those found in Bernstein, Brewer et al 27 COSI (Table III, Fig. 3)COSI means at pretest were not significantly different between groups (Cohen's d, Goal 1: 0.10, Goal 2: 0.10, Goal 3: 0.39).…”
Section: Outcome Measuressupporting
confidence: 90%
“…Planned analyses of group differences were not significant at 1-week posttreatment or 2 months posttreatment, though small effect sizes were seen (0.28 and 0.36). The pattern of these results follows the trend seen in Bernstein, Brewer et al 27 which showed medium effect sizes for improvements in speech recognition.…”
Section: Outcome Measuressupporting
confidence: 82%
“…Patients who demonstrate little improvement in speech recognition in the early post-operative period might require additional interventions such as speech-language pathologist-led auditory rehabilitation and computer-based auditory training activities, which have been demonstrated to improve speech recognition in the early post-implantation period. [56][57][58][59][60] Long-term evaluation of speech recognition is necessary for all patients as individual patient outcomes may demonstrate wide variation from group means. 61,62 Although speech recognition is considered to be the standard for measuring outcomes in CI users, word and sentence recognition measured in a controlled environment does not assess communication abilities in more complex environments and, therefore, does not reflect CI users' abilities in real-world listening situations.…”
Section: Discussionmentioning
confidence: 99%
“…For clinicians, these findings underscore the importance of regular use of the device and repeated evaluation in the early post‐operative period. Patients who demonstrate little improvement in speech recognition in the early post‐operative period might require additional interventions such as speech‐language pathologist‐led auditory rehabilitation and computer‐based auditory training activities, which have been demonstrated to improve speech recognition in the early post‐implantation period 56–60 . Long‐term evaluation of speech recognition is necessary for all patients as individual patient outcomes may demonstrate wide variation from group means 61,62 …”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies (n = 13) were repeated measure studies, examining a single uncontrolled cohort [13,20,[28][29][30][31][32][33][34][35][36][37][38]. A total of seven studies were randomized controlled trials or crossover trials [39][40][41][42][43][44][45], and four studies were nonrandomized controlled trials or cohort studies [21,28,46,47].…”
Section: Study Characteristicsmentioning
confidence: 99%